Fingerprint pattern of major ethnic groups among students of Ibrahim Badamasi Babangida University Lapai, Nigeria - Mohammed Chado Isah; Alfa Maali Muhammed; Fatima Isah Yabagi; Safiya Yunusa Mohammed (Journal of Tropical Life Science, 2020)
This study is aimed at identifying fingerprint pattern of major ethnic groups among the students of Ibrahim Badamasi Babangida University (IBBU) Lapai, which can be helpful in resource management for Niger State of Nigeria. The students were grouped into Nupe, Gwari, Kambari and Non-Nigerlites. Occasions for specific ethnic groups were target for data collection which exclude exclusion criteria. The types of finger print patterns considered include Ulnar Loop, Radial Loop, Plain Arch, Tented Arch and Accidental Whorl, Plain Whorl, Double Loop Whorl and Central Pocket Whorl. The respondents’ fingerprints were collected using inked stamp pad, printed onto designated potions on coded paper. The data collected were represented in percentage occurrence of the fingerprint patterns for each group. Ulnar Loop was the commonest fingerprint pattern among the students of IBBU Lapai. Also common to the groups of the students are absence of Double Loop Whorl on the right ring finger, left and right little fingers as well as Tented Arch not on the right Thumb of the students. The finger print marker for the groups were absence of Double Loop Whorl on the right ring finger and absence of Tented Arch on the left Thumb of Nupe, absence of Double Loop Whorl on the left index fingers of Gwari, Tented Arch not on left and right little fingers of Kambari speaking people studying in IBBU Lapai, those of the Non-Nigerlite students of IBBU Lapai lack Tented Arch on all their fingers and Double Loop Whorl not on the right index finger.